Usos ilícitos que pueden darse a la trasplantación de huellas dactilares en documentos privados (2018)
The fingerprints of a person allows him to identify himself, therefore, they must be protected against the attempt of obtaining, accessing or revealing for the undue ends. Since ancient times, there are techniques and methodsthat can be used for the transplantation of fingerprints with different fines.Criminology, for example, uses the techniques of late fingerprint transplantation in order to preserve the evidence, as well as, to be able to analyze and make thepertinent comparisons in their laboratories. While criminals use fines of theft and identity theft, which allows committing crimes such as falsification of private documents, concealment of true identity, theft, scams, among others. The Colombian legal system contains provisions aimed at penalizing such activities, as well as mechanisms to protect the integrity of the data provided by citizens. Due to the technological progress that exists today, fingerprints can be transplanted more easily, due to this, the databases that contain them merit greater protection and security